Dosing of interventions and interdisciplinary care in the rehabilitation process of children and adolescents with cerebral palsy in Argentina - Escobar Zuluaga, Leidy Johana (2025)
Objective. To compare the differences between the characteristics of rehabilitation processes (dosage and interdisciplinary care) and the clinical and sociodemographic characteristics of children and adolescents with cerebral palsy (CP) attending rehabilitation centers in Argentina. Population and methods. This is a cross-sectional study with sequential sampling. Children and adolescents aged 2 to 19 with CP from 15 rehabilitation centers were included. Questionnaires and information from medical records were used. The chi-square test with Fisher or Man-Whitney correction was used to compare the differences between the response variables (dose and interdisciplinary care) with age, severity, social security, type of institution, and socioeconomic level (SEL). A bivariate analysis with odds ratio was performed to measure the magnitude of the association. Results. A total of 267 participants were included. In terms of dose, the median was 3.5 hours of therapy per week. Children of lower-middle SEL, without social security, and attending public institutions received fewer hours of therapy. No differences were found in the number of hours according to age and severity level; regarding the number of disciplines, in most children older than 11 years fewer disciplines were involved in the therapeutic process. Conclusion. Statistically significant differences in dosing and interdisciplinary care were found concerning age groups, SES, access to social security, and type of institution attended, but not with the level of motor impairment.